Improving the genetic system for Halorubrum lacusprofundi to allow in-frame deletions - Gebhard, L. Johanna; Duggin, Iain G.; Erdmann, Susanne (Frontiers in Microbiology, 2023)
Halorubrum lacusprofundi is a cold-adapted halophilic archaeon isolated from Deep Lake, Antarctica. Hrr. lacusprofundi is commonly used to study adaptation to cold environments and thereby a potential source for biotechnological products. Additionally, in contrast to other haloarchaeal model organisms, Hrr. lacusprofundi is also susceptible to a range of different viruses and virus-like elements, making it a great model to study virus-host interactions in a cold-adapted organism. A genetic system has previously been reported for Hrr. lacusprofundi; however, it does not allow in-frame deletions and multiple gene knockouts. Here, we report the successful generation of uracil auxotrophic (pyrE2) mutants of two strains of Hrr. lacusprofundi. Subsequently, we attempted to generate knockout mutants using the auxotrophic marker for selection. However, surprisingly, only the combination of the auxotrophic marker and antibiotic selection allowed the timely and clean in-frame deletion of a target gene. Finally, we show that vectors established for the model organism Haloferax volcanii are deployable for genetic manipulation of Hrr. lacusprofundi, allowing the use of the portfolio of genetic tools available for H. volcanii in Hrr. lacusprofundi.